Proceedings of the 50th Hawaii International Conference on System Sciences (2017) 2017
DOI: 10.24251/hicss.2017.596
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Propensity for Enterprise Cloud Computing Adoption

Abstract: Cloud computing (CC)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
5
0
1
Order By: Relevance
“…For internal adoption, the first internal factor is investment desire that explained by . second of the internal factor is top management that asserted by Alharbi et al (2016) and Kyriakou et al (2017). Firm size is the third internal factor that is expressed by Son, Lee, Lee, & Chang (2011).…”
Section: Cloud Computing Adoptionmentioning
confidence: 96%
See 1 more Smart Citation
“…For internal adoption, the first internal factor is investment desire that explained by . second of the internal factor is top management that asserted by Alharbi et al (2016) and Kyriakou et al (2017). Firm size is the third internal factor that is expressed by Son, Lee, Lee, & Chang (2011).…”
Section: Cloud Computing Adoptionmentioning
confidence: 96%
“…Third of the external effects of cloud computing adoption is cloud providers stated by Cruzes (2015) and Singh & Randhawa (2015). Business partners in the fourth external effects that are mentioned by Bogataj Habjan & Pucihar (2017) and Kyriakou et al (2017). Competitors and cloud service brokers are the last that is mentioned by .…”
Section: Cloud Computing Adoptionmentioning
confidence: 98%
“…Oliveira et al (2014) [23] found that top management support highly affects the adoption in the Portuguese service sector and companies; Alkhalil et al (2017) [47] reported that it highly affects the adoption in English SMEs; Deil & Brune (2017) [48] stated that top management support highly affects the adoption German SMEs. However, Oliveira et al [23,46,49,50] proved that top management support is not significantly important, in the Portuguese manufacturing sector, UK companies, ceramic and cement sectors in six European countries (Germany, France, Italy, Poland, Spain, and the UK) and Jordan companies. Top management support is more likely to affect the service sector declared by Oliveira et al (2014) and SMEs stated by Alkhalil et al (2017) [23,47].…”
Section: -2-implication and Explanation Of Findings And Comparison With Other Studiesmentioning
confidence: 99%
“…Por además del método Delphi deben considerarse otros métodos alternativos, con menos ventajas, pero que pueden emplearse de acuerdo con los resultados esperados: grupos focales 19 , votación en listas cortas, reuniones virtuales para discusión abierta, tormenta de ideas, etc. Entre otros menos comunes, pero que pueden ser efectivos, se encuentran el proceso de jerarquía analítica 20 y los basados en algoritmos computacionales de predicción analítica 20,21 .…”
Section: Delphi En La Saludunclassified